Ultrasonographic characterization of of the abdominal and pelvic organs of the spectacled bear (Tremarctos ornatus) in captivity - Talavera C., Camila (2021)
The aim of this study was to characterize ultrasound images of the abdominal and pelvic organs of the spectacled bear (Tremarctos ornatus) in captivity. Eight adult specimens (3 males and 2 females) from the Patronato del Parque de las Leyendas zoo (Lima, Peru) and two males from the Mundo Natural Rescue Center (Tingo María, Peru) were evaluated. A MyLab OneVet (Esaote) ultrasound machine with a 4-9 MHz convex transducer was used. The kidney was found to have a multilobed shape, similar to that of other ursids and domestic bovines. The ultrasonographic and topographic characteristics of the abdominal organs, as well as of the testes, are similar to those described in other domestic carnivorous species, with variations proportional to the larger size of the species. The testis has a little marked and discontinuous mediastinum testis.